Study of the tribological properties of fly ash cenosphere particulate reinforced LM6 (Al-Si12) matrix alloy composites produced by stir casting method - Tanusree Bera; Samir K. Acharya (Jurnal Tribologi, 2018)
Stir casting is an economical and simplest method for the production of metal matrix composites (MMCs). In this process, the mixing of the reinforcement particles into the molten metal bath is achieved by stirring. After stirring, the molten metal poured into the desired shape mould and allowed for solidification. In this study, LM6 (Al-Si12) matrix reinforced with fly ash cenosphere particulates produced MMCs through the stir casting method. The friction and wear behaviour were studied for LM6 (Al-Si12)/cenosphere composites by using pin-on-disc wear tester under dry sliding condition. The friction and wear tests were carried out at different weight percentages of cenosphere (wt. % c/s) under various loads and sliding velocity. The results showed that the wear resistance of LM6 (Al-Si12) / cenosphere composites is better than of LM6 (Al-Si12) matrix alloy. The specific wear rate and the coefficient of friction decrease as the load increases. The worn mass loss of the composites increases rapidly with the increase of the applied load. Scanning electron microscopy (SEM) studies reveal the presence of abrasive wear mechanisms.